Strengthening Human Resource Readiness And Infrastructure To Improve Simrs Adoption: A Literature Review - Riswanto (PT PUSTAKA CENDEKIA GROUP, 2025)
This study examines the relationship between human resource readiness and the adoption and successful implementation of the Hospital Management Information System (SIMRS), as well as how the competence of health workers interacts with the availability of hospital infrastructure and management strategies. The method uses a systematic literature review or scoping review to map the empirical evidence of the last ten years. Structured searches were conducted on Scopus and Web of Science, and Google Scholar with a combination of keywords related to SIMRS, human resource readiness, competencies, infrastructure, adoption, successful implementation, training, and management strategies, including Indonesian equivalents. Articles are selected through title and abstract screening, full-text review, and concise quality assessment based on design and clarity of method. The data was extracted including hospital settings, user samples, variable definitions, instruments, and key findings, and then synthesized thematically narratively. Results show that human resource readiness, especially tiered training, organizational culture support, and perception of convenience and usefulness, correlates with more consistent acceptance and use of SIMRS. A reliable infrastructure amplifies competency impact, while weak networks and devices lower satisfaction, trigger double logging, and hinder feature utilization. The most consistent strategies to improve output include change management, strengthening IT support, standardizing devices, network investment, and ongoing funding planning. This synthesis formulates the proposition that the success of SIMRS is the result of the synergy of human capacity and technological capacity in daily work practices.